Sistem Peradilan Hukum Acara Pidana Berdasarkan Undang-Undang Nomor 20 Tahun 2025 Tentang Kitab Undang-Undang Hukum Acara Pidana Berbasis Sistem Teknologi Informasi - Abdul Hayy Nasution (SENTRI: Jurnal Riset Ilmiah, 2026)
Recent developments in the reform of Indonesia's criminal procedural law have strengthened the recognition of electronic evidence through its regulation in the new Criminal Procedure Code. Law Number 20 of 2025 concerning the Criminal Procedure Code explicitly recognizes electronic evidence as one of the admissible forms of evidence in criminal proceedings. This study examines the application of the criminal procedural law system under Law Number 20 of 2025 concerning the Criminal Procedure Code through the Information Technology System, as well as the implementation of the criminal procedural law system under the same law through the Information Technology System. This research employs a normative legal research method. The objectives of this study are to analyze the application of the criminal procedural law system under Law Number 20 of 2025 concerning the Criminal Procedure Code through the Information Technology System and to examine its implementation within the framework of the Information Technology System.